Desafios para a universalização do abastecimento de água no município de Breves-Pará - ROCHA, Caroline Silva Nepomuceno (Universidade Federal do Pará, 2019)
The objective of this research is to analyze the challenges related to the implementation of the universalization of water supply for the population of the Municipality of Breves, in the Marajó Archipelago, State of Pará, compared to what is foreseen in the current legislation of the sector. The theoretical basis of the work is anchored in the following axes. First, the evolution of the sanitation sector in Brazil is discussed. Then the planning of the sector comprising the instrument at the federal, state and municipal levels. Then, the issue of water supply management, efficiency, sustainability, information system, indicators, regulation and ends with the participation and social control of the sector. The methodology of the work is descriptive, bibliographical and documentary. The stages were defined for the evaluation of the services rendered, the demographic evolution and its impact on the evolution of services followed by the propositions for structuring the sector in the Municipality of Breves. Results obtained in the research show that the legal obligations of the municipality in the area of infrastructure are insufficient, in the aspect of economic, financial sustainability, the system is deficient, and the impact on the population in the next 20 years is deeply negative considering the management of the infrastructure and the instruments of municipal planning. The research proposed a set of actions for the structuring of the water supply sector in the municipality covering the following aspects: elaboration and / or updating of the basic sanitation plan involving its essential dimensions, delegation of regulation, efficiency, social control, creation of an administrative body to coordinate the reformulation of the plan and the treatment of information in the sanitation sector of the Municipality of Breves. The research found that the greatest challenge for municipal management in the sanitation sector is to promote the universalization of the water supply for the population, fulfilling what was established in the current legislation